Analisis Kebutuhan Rohani dan Strategi PAK bagi Remaja dan Pemuda di Gereja Agape - Yuwantri Yuwantri; Hendro Hendro; Gabriel Stefanofit Akwan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study discusses the spiritual development of adolescents and Christian youth in facing the challenges of the digital age. The focus of this research is on the role of parents, churches, and Christian educators in shaping the spirituality of Christian youth and youth. The results of the study show that parents, churches, and Christian educators have a very important role in guiding Christian youth and youth in their faith journey. Digital literacy teaching strategies based on Christian values and engaging adolescents and youth directly in the ministry process are some of the ways that can be done to strengthen their faith and character. In addition, this study emphasizes the importance of sustainable and contextual spiritual coaching in order to be able to answer spiritual needs in the midst of the rapid flow of information and the influence of modern culture. The Church is also expected to be able to provide a safe space for dialogue for youth and youth to express their struggles of faith. Thus, comprehensive and collaborative coaching can help create a resilient young generation of Christians, rooted in God's word, and able to face the various moral and spiritual challenges of today.